Optimizing Portfolio Performance at PT. IAI Financial - Devika Putrihadiningrum; Cynthia Eka Violita (GREENOMIKA, 2023)
The aim of the research carried out by the author is to analyze the composition of investment portfolios (asset allocation) that can provide the most optimal returns to provide high returns with certain risks. The approach used in this research is the case study method. The data analysis used is a descriptive method and a quantitative method, which is limited to the Pension Fund investment portfolio data at PT. IAI Financial for the 2019-2022 period. This research shows that the first proportion shows the average return generated is 12.5 with the same risk, namely 1.44. The second proportion uses the Markowitch approach. The average return generated is 5.20 with the same risk, namely 1.44. Based on the analysis of optimizing investment instruments at PT. IAI Financial above shows that the IAI Pension Fund investment results have not been able to provide optimal results, so the financial manager at PT. IAI Financial needs to look for new investment alternatives with proportions that can increase risk and return.